Effect of User Involvement Peak Management Support Training and Education Program on the Performance of Accounting Information Systems Star Hotels 4 and 5 - DEWI, Ni Komang Ayu Triana; KAWISANA, Putu Gede Wisnu Permana; LARASDIPUTRA, Gde Deny (PT Keberlanjutan Strategis Indonesia, 2023)
The background of this research is the lack of skills and knowledge that users of accounting information systems have due to the presence of Covid-19. During Covid-19 users of accounting information systems in 4 and 5 star hotels experienced a decrease in hotel revenue. In this study using quantitative methods data was collected using a questionnaire technique. Respondents in this study were 60 people who met the criteria. Three hypotheses were formulated and tested using multiple linear regression analysis. The results of this study are user involvement and top management support have a positive and significant effect on SIA while training and education have a positive effect.